2014
DOI: 10.1371/journal.pntd.0002616
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing Reveals Regulation of Distinct Aedes microRNAs during Chikungunya Virus Development

Abstract: BackgroundApplication of genomics and Next Generation sequencing has led to the identification of new class of cellular functional molecules, namely, small RNAs. Of the several classes of ncRNAs (non-coding RNA), microRNAs have been demonstrated to exert determinative influence on various cellular processes. It is becoming abundantly clear that host/vector/pathogen encoded microRNAs impact eventual pathogenesis. In this context, the participation of vector based microRNAs in disease transmission and pathogen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 40 publications
1
77
1
Order By: Relevance
“…miR‐283‐5p was upregulated and miR‐1‐3p was absent in an Ae. albopictus cell line after exposure to Chikungunya virus (Shrinet et al ., ). Similarly, in our study miR‐283‐5p was upregulated and miR‐1‐3p was downregulated in diapause pharate larvae.…”
Section: Discussionmentioning
confidence: 97%
“…miR‐283‐5p was upregulated and miR‐1‐3p was absent in an Ae. albopictus cell line after exposure to Chikungunya virus (Shrinet et al ., ). Similarly, in our study miR‐283‐5p was upregulated and miR‐1‐3p was downregulated in diapause pharate larvae.…”
Section: Discussionmentioning
confidence: 97%
“…Over the past few years, mosquito miRNAs have been reported to be prominent gene regulatory factors in response to pathogen such as DENV, Chikungunya virus (CHIKV) and West Nile Virus (WNV) (Campbell et al ., ; Mayoral et al ., ; Shrinet et al ., ; Liu et al ., ). In our study, a total of 85 miRNAs were identified and with three regulated miRNAs upon DENV infection in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs are endogenously encoded small noncoding RNAs which govern the gene expression post‐transcriptionally. Several studies based on miRNA mediated gene regulation proved the potential of miRNA during disease conditions . In our previous study on CHIKV infected primary human synovial fibroblasts, we reported the suppression of pro‐inflammatory immune responses through the increased expression of miR‐146a .…”
Section: Discussionmentioning
confidence: 94%
“…Several studies based on miRNA mediated gene regulation proved the potential of miRNA during disease conditions. 17,19,[29][30][31][32] In our previous study on CHIKV infected primary human synovial Note: The DEMs which were not analyzed through bioinformatics tool were marked with * (hsa-miR-5692c/hsa-miR-5692b) since, they were only documented in one target prediction database. Abbreviations: CHIKV: Chikungunya virus; DEM: differentially expressed microRNA; miRNA: microRNA.…”
Section: Discussionmentioning
confidence: 99%